CONFLICT IN SOUTH CHINA SEA BETWEEN CHINA AND PHILIPPINES - Seniwati, Seniwati; Hudzon, Muhammad Rofif; Burhanuddin, Agussalim (Triwikrama: Jurnal Ilmu Sosial, 2024)
The South China Sea sovereignty dispute between China and the Philippines has been ongoing for decades, with tensions peaking after China took over Mischief Reef in 1995. The dispute involves overlapping claims over a strategic and resource-rich area, including oil, natural gas, and marine products. The method used in this research is library research, which is a method of collecting data through academic literature, journals, books, and relevant reference sources. The theory in this research is to explore International Conflict Theories & History of South China Sea. Which International Conflict Theories highlight the important role of conflict in driving social change, involves cross-border actors, and requires a comprehensive approach to prevention and resolution at the global level. The History of South China Sea covers important trade routes, countries' sovereignty claims, and centuries of geopolitical tensions due to economic and military interests. The South China Sea dispute involves multiple countries with overlapping territorial claims and resource interests. The conflict is fueled by huge economic potential, such as oil, gas and vital trade routes. Growing tensions, especially between China and the Philippines, require a careful diplomatic solution. To prevent a more dangerous escalation of the conflict, international cooperation is needed from each country involved as well as from outside to maintain and stabilize regional security in the South China Sea Region.